2021
DOI: 10.1007/s13311-020-00978-4
|View full text |Cite
|
Sign up to set email alerts
|

The Dysregulation of OGT/OGA Cycle Mediates Tau and APP Neuropathology in Down Syndrome

Abstract: Protein O-GlcNAcylation is a nutrient-related post-translational modification that, since its discovery some 30 years ago, has been associated with the development of neurodegenerative diseases. As reported in Alzheimer’s disease (AD), flaws in the cerebral glucose uptake translate into reduced hexosamine biosynthetic pathway flux and subsequently lead to aberrant protein O-GlcNAcylation. Notably, the reduction of O-GlcNAcylated proteins involves also tau and APP, thus promoting their aberrant phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 124 publications
2
12
0
Order By: Relevance
“…These data suggest that the O-GlcNAcylation profile was completely opposite to that examined in the hippocampus and that a direct competition between O-GlcNAcylation/phosphorylation may only occur at brain level, while peripheral alterations are mainly associated with the increase of protein O-GlcNAcylation. These results follow previous data collected in Down syndrome mice [ 55 ] and are in line with the notion that the aberrant increase of peripheral O-GlcNAcylation levels might be related to insulin resistance and to hyperglycemia-induced glucose toxicity [ 56 ]. Afterwards, we evaluated potential alterations occurring on the O-GlcNAc enzymatic machinery with the aim of assessing whether the reduced levels of O-GlcNAcylated proteins in the hippocampus of HFD mice could be the result of the altered OGT/OGA functionality.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These data suggest that the O-GlcNAcylation profile was completely opposite to that examined in the hippocampus and that a direct competition between O-GlcNAcylation/phosphorylation may only occur at brain level, while peripheral alterations are mainly associated with the increase of protein O-GlcNAcylation. These results follow previous data collected in Down syndrome mice [ 55 ] and are in line with the notion that the aberrant increase of peripheral O-GlcNAcylation levels might be related to insulin resistance and to hyperglycemia-induced glucose toxicity [ 56 ]. Afterwards, we evaluated potential alterations occurring on the O-GlcNAc enzymatic machinery with the aim of assessing whether the reduced levels of O-GlcNAcylated proteins in the hippocampus of HFD mice could be the result of the altered OGT/OGA functionality.…”
Section: Resultssupporting
confidence: 92%
“…Although most of the pathological alterations observed in HFD mice are similar to those of other neurodegeneration models, the mechanisms underlying disturbances of O-GlcNAc homeostasis in the brain of HFD mice have different origins. We previously observed in the hippocampus of a mouse model of DS, the hyperactivation of OGA [ 55 ], but HFD mice did not show any significant increase in the removal of O-GlcNAc moiety. Rather the attention must be focused on the observed alteration of the hippocampal metabolic status associated with the development of insulin resistance.…”
Section: Discussionmentioning
confidence: 93%
“…Here also we observed that the reduction of autophagy, demonstrated by altered LC3 II/I, Atg12/5 and Atg7 levels, contributed to the increase of oxidative stress, to defective UPS and to the alteration of early synaptic proteins in Ts65Dn mice [ 63 , 187 ]. Similarly, the alteration of autophagy was also observed in Ts2Cje mice [ 56 ].…”
Section: Stress Responses In Down Syndrome Brainmentioning
confidence: 90%
“…Due to the important role of insulin signaling pathway in the regulation of brain functions, the development of brain insulin resistance seems to be highly implicated in the promotion of AD-like dementia in DS, representing a key pathological event. Moreover, recent evidence from our lab suggest a role for the nutrient-related dynamic changes of O-GlcNAcylation in the progression of DS neuropathology [ 56 ].…”
Section: Brain Pathology In Down Syndromementioning
confidence: 99%
See 1 more Smart Citation